The Experience of Orgasmic Pleasure during Partnered and Masturbatory Sex in Women with and without Orgasmic Difficulty. Issue 6 (18th August 2019) - Rowland, David; Donarski, Allyse; Graves, Valerie; Caldwell, Corydon; Hevesi, Barbara; Hevesi, Kriszta
Abstract: Pleasure is critically important to the experience of sexual behavior, yet few studies have examined factors that influence it. We explored orgasmic pleasure during masturbation and partnered sex in women with and without orgasmic difficulty, as well as the mutual influence of each type of activity on the other. Data were collected from 2059 women through online surveys and paper-and-pencil tests in both the USA and Hungary. Among women who both masturbated and had partnered sex, orgasmic pleasure was higher during partnered sex. Although women with orgasmic difficulty exhibited a similar pattern of greater pleasure during partnered sex, they reported lower pleasure during partnered sex than women without orgasmic difficulty. Women struggling most to reach orgasm were likely to view masturbation as equally or more satisfying than partnered sex. Several covariates were relevant to pleasure during partnered sex, including the importance of sex, the frequency of partnered sex, and the relationship quality, affirming the idea that relational factors play a critical role in orgasmic pleasure in women. Pleasure during masturbation was associated with higher age, frequency of masturbation, and shorter latencies to orgasm, suggesting that pleasure during masturbation was related to greater experience with masturbation and greater efficiency in reaching orgasm.